Smart working is not so smart: Always-on lives and the dark side of platformisation. (1st January 2021) - Risi, Elisabetta; Pronzato, Riccardo
Abstract : This article investigates the lived experiences of remote workers during the Italian lockdown, and the role of digital platforms in their working and everyday life activities, as well as the consequences of home confinement measures on personal and working conditions. Drawing on 20 in-depth semi-structured interviews, the paper's findings suggest that, following a massive extension of transmedia work, remote workers experienced a 'fractured' and 'always-on' life. During the lockdown, the ever more pervasive role of digital media favoured the convergence of different spaces and times into the home, the erosion of the distinction between private and professional life and the exacerbation of previous social inequalities, especially inequalities in relation to gender and digital access. In this scenario, platform and surveillance capitalist logics were further reinforced, while 'presence bleed' in the experiences of workers increased.